2021
DOI: 10.1111/tbed.14337
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic assessment to quantify the risk of introduction of African swine fever virus to Taiwan via illegal pork products carried by international travellers

Abstract: The current study quantified the risk of releasing African swine fever virus (ASFV) into Taiwan from pork products illegally carried by international travellers from 157 countries or territories through six international airports and three international seaports.The association between various factors and the number of pork products detected by the border control authorities was also examined. The risk was estimated with a stochastic process after modelling the number of undetected illegal pork products, proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…In Taiwan and Japan, the primary risk of ASF introduction is associated with border control inspections, as studies indicate ASFV can be detected in pork products brought by travelers [ 37 , 38 , 39 , 40 ]. Empirical evidence from Taiwan reveals a notable increase in the detection of illegal pork products carried by international travelers, particularly peaking in January and February [ 39 ].…”
Section: Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Taiwan and Japan, the primary risk of ASF introduction is associated with border control inspections, as studies indicate ASFV can be detected in pork products brought by travelers [ 37 , 38 , 39 , 40 ]. Empirical evidence from Taiwan reveals a notable increase in the detection of illegal pork products carried by international travelers, particularly peaking in January and February [ 39 ].…”
Section: Strategiesmentioning
confidence: 99%
“…In Taiwan and Japan, the primary risk of ASF introduction is associated with border control inspections, as studies indicate ASFV can be detected in pork products brought by travelers [ 37 , 38 , 39 , 40 ]. Empirical evidence from Taiwan reveals a notable increase in the detection of illegal pork products carried by international travelers, particularly peaking in January and February [ 39 ]. Despite pigs in domestic farms testing negative for ASF in both Taiwan and Japan, a persistent threat arises from travelers transporting pork-related products that may harbor ASFV.…”
Section: Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, ASF-contaminated pork products are frequently detected at international ports, and the risk of ASF entry is estimated to be high ( 39 ). Similarly, quantitative risk assessment studies conducted in Taiwan have shown a very high risk of ASFV introduction ( 40 ). A dead pig that washed ashore in the territory was recorded as an ASF-positive individual in the EMPRES-i database ( 7 , 40 ).…”
Section: Asf Subregional Update In East Asiamentioning
confidence: 99%
“…Similarly, quantitative risk assessment studies conducted in Taiwan have shown a very high risk of ASFV introduction ( 40 ). A dead pig that washed ashore in the territory was recorded as an ASF-positive individual in the EMPRES-i database ( 7 , 40 ).…”
Section: Asf Subregional Update In East Asiamentioning
confidence: 99%